2015
DOI: 10.1037/xap0000042
|View full text |Cite
|
Sign up to set email alerts
|

Advertising energy saving programs: The potential environmental cost of emphasizing monetary savings.

Abstract: Many consumers have monetary and environmental motivations for saving energy. Indeed, saving energy produces both monetary benefits, by reducing energy bills, and environmental benefits, by reducing carbon footprints. We examined how consumers' willingness and reasons to enroll in energy-savings programs are affected by whether advertisements emphasize monetary benefits, environmental benefits, or both. From a normative perspective, having two noteworthy kinds of benefit should not decrease a program's attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
3
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(147 citation statements)
references
References 27 publications
9
124
3
5
Order By: Relevance
“…Bolderdijk and colleagues (2013) found that, to promote a tire check among car drivers (to reduce gasoline usage), environmental appeals were more effective as compared to monetary appeals. Schwartz, Bruine de Bruin, Fischhoff, and Lave (2015) found similar results when gauging the willingness to enrol in an energy saving program. In another study, Asensio and Delmas (2015) found that the combination of environmental and health-related information outperformed financial information in reducing electricity energy consumption over a period of eight months.…”
Section: Understanding the Differences Between Monetary And Environmesupporting
confidence: 64%
“…Bolderdijk and colleagues (2013) found that, to promote a tire check among car drivers (to reduce gasoline usage), environmental appeals were more effective as compared to monetary appeals. Schwartz, Bruine de Bruin, Fischhoff, and Lave (2015) found similar results when gauging the willingness to enrol in an energy saving program. In another study, Asensio and Delmas (2015) found that the combination of environmental and health-related information outperformed financial information in reducing electricity energy consumption over a period of eight months.…”
Section: Understanding the Differences Between Monetary And Environmesupporting
confidence: 64%
“…Monetary gains, however may be effective only when perceived as worth the effort (Dogan et al, 2014). If the monetary gains involved are rather small, monetary framing has negative effects on the target behaviour (Asensio & Delmas, 2015;Bolderdijk et al, 2013;Schwartz et al, 2015). Due to inconclusive evidence so far, we assume:…”
Section: Framing Effects On the Target Behaviourmentioning
confidence: 95%
“…Evidently, the effects of environmental or monetary framing depend strongly on the perceived behavioural gains. Environmental gains are perceived worthwhile, independent of their size (Bolderdijk et al, 2013;Dogan et al, 2014;Schwartz et al, 2015). Monetary gains, however may be effective only when perceived as worth the effort (Dogan et al, 2014).…”
Section: Framing Effects On the Target Behaviourmentioning
confidence: 97%
See 1 more Smart Citation
“…Frugal consumers may be motivated by financial incentives, at least for as long as they are being provided (Fischer 2008). However, pro-environmental consumers may be turned off by financial incentives, because it undermines the "warm glow" of pro-environmental motivations (Schwartz et al 2015;Taufik et al 2014). Social rewards may therefore be more effective than financial rewards (Agrawal et al 2014;Handgraaf et al 2013).…”
Section: Struggles To Meet the Maxim Of Relationmentioning
confidence: 99%